Cause analysis and mechanism study of cracks in drilling collars. (November 2019) - Zhong, Zhenqian; Li, Yunling; Liu, Yingchun; Bao, Lei; Tian, Zhiling
Abstract: A drill collar with material of 0Cr20Mn21Ni2N serviced in a coastal continental shelf oilfield, has cracked and leaked after a short period of working. Failure analysis of drill collar was performed by a series of experiments, including Chemical analysis, Fractographic analysis, Microstructural analysis, Intergranular attack test, Mechanical property, Residual stress test, EBSD analysis of relationship between crack propagation and crystal orientation. The fractographic observations showed crack initiated from the inner surface and extended to outer surface by the mode of inter-granular and quasi-cleavage trans-granular fracture, many branch cracks were produced during its propagation. Serious corrosion morphology was found both on the inner surface of drill collar and fracture surface, and S and Cl were detected in the corrosion products. The above evidence indicates that the cracking failure mode of drill collar can be described as the Stress Corrosion Cracking (SCC) of austenitic stainless steel. The causes of stress corrosion cracks are attributed to three aspects. Firstly, the microstructures of the materials are sensitized seriously, and there are many precipitated phases at grain boundaries, which result in chromium depletion in the grain boundaries and decrease of corrosion resistance of the materials. Secondly, during service the mud water on the inner surface of drill collar is composed of seawater containing chloride and sulfate radical, which provides corrosive environment for materials. Thirdly, the residual tensile stress on the inner surface of the drill collar reaches 112 MPa, which hinders the formation of passive film on the surface of stainless steel and has adverse effect on the corrosion resistance of the material. In addition, the mechanism of crack formation was studied by EBSD. Corrosion pits of inner-surface of drill collar is intergranular corrosion, which first occurs at random grain boundaries with high misorientation angles, rather than at special grain boundaries such as Σ3. SCC crack initiates from the corrosive pit and propagate along the grain boundary first and gradually transit to transgranular growth with Zigzag fracture morphology along {111}〈110〉 slip system, which proves SCC transgranular crack propagation obeys the slip corrosion mechanism. Highlights: The failure for stainless steels of Fe-Cr-Mn-N system has been seldom reported by literature. The failure is attributed to sensitized microstructure, corrosive environment, and residual tensile stress. The mechanism of SCC formation is also studied, which proves crack propagation obeys the slip corrosion mechanism.